Cost and Performance Analysis of Integrity Validation Techniques for a Distributed Database - Ibrahim, Hamidah (Universiti Putra Malaysia Press, 2002)
A principal problem with the use of integrity constraints for monitoring the integrity of a dynamically changing database is their cost of evaluation. This cost which is associated with the performance of the checking mechanisms is the main quantitative measure which has to be supervised carefully. We have developed an integrity constraint subsystem for a relational distributed database (SICSDD) which consists of several techniques that are necessary for efficient constraint checking, particularly in a distributed environment where data distribution is transparent to the application domain. In this paper, we will show how these techniques have effectively reduced the cost of constraint checking in such a distributed environment.